(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
“It will be the first time I suck a woman’s cock” (Almodóvar 99). This phrase is a significant and representative sample of the genre discourse in which Pedro Almodóvar places the characters in “All About My Mother,” his latest film, as well as in the bulk of his film production (note).